MODEL OF IMPROVING HUMAN RESOURCE PERFORMANCE THROUGH PERSON JOB FIT AND SPIRITUAL INTELLIGENCE OF EMPLOYEES WITH MEDIATION OF PROFESSIONAL COMPETENCE AT DEPARTMENT OF AGRICULTURE, FISHERIES AND FOOD OF SEMARANG REGENCY - Tri Hastuti Mustiko Sari; Budhi Cahyono (IJIBE (International Journal of Islamic Business Ethics), 2017)
A person of human resources has important meaning for a company. Therefore the company must be able to maintain the level of satisfaction. A human resource who is satisfied with his work will show a positive attitude in working. Thus, the company needs to maintain employee satisfaction by providing optimal support. Human resources are satisfied with work which is the beginning of a very important success for the company (Robbins, 2016). Human resources in an organization have a function in every execution of tasks that must be done, one of which is the function of service, where in government agencies it is one thing that must be filled by human resources to anyone who needs government services. If the services provided are not satisfactory, it will get a bad impression in the eyes of the people. This is what makes good human resource performance is needed in government agencies.